Safety and Immunogenicity of the PRAME Cancer Immunotherapeutic in Patients with Resected Non-Small Cell Lung Cancer: A Phase I Dose Escalation Study - Pujol, Jean-Louis; De Pas, Tommaso; Rittmeyer, Achim; Vallières, Eric; Kubisa, Bartosz; Levchenko, Eugeny; Wiesemann, Sebastian; Masters, Gregory A; Shen, Robert; Tjulandin, Sergei A; Hofmann, Hans-Stefan; Vanhoutte, Nicolas; et al. (Journal of thoracic oncology, 2016)
Adjuvant platinum-based chemotherapy is standard treatment for surgically resected stage II to IIIA NSCLC, but the relapse rate is high. The preferentially expressed antigen of melanoma (PRAME) tumor antigen is expressed in two-thirds of NSCLC and offers an attractive target for antigen-specific immunization. A phase I dose escalation study assessed the safety and immunogenicity of a PRAME immunotherapeutic consisting of recombinant PRAME plus proprietary immunostimulant AS15 in patients with surgically resected NSCLC (NCT01159964). Patients with PRAME-positive resected stage IB to IIIA NSCLC were enrolled in three consecutive cohorts to receive up to 13 injections of PRAME immunotherapeutic (recombinant PRAME protein dose of 20 μg, 100 μg, or 500 μg, with a fixed dose of AS15). Adverse events, predefined dose-limiting toxicity, and the anti-PRAME humoral response (measured by enzyme-linked immunosorbent assay) were coprimary end points. Anti-PRAME cellular responses were assessed. A total of 60 patients were treated (18 received 20 μg of PRAME, 18 received 100 μg of PRAME, and 24 received 500 μg of PRAME). No dose-limiting toxicity was reported. Adverse events considered by the investigator to be causally related to treatment were grade 1 or 2, and most were injection site reactions or fever. All patients had detectable anti-PRAME antibodies after four immunizations. The percentages of patients with PRAME-specific CD4-positive T cells were higher at the dose of 500 μg compared with lower doses. No predefined CD8-positive T-cell responses were detected. The PRAME immunotherapeutic had an acceptable safety profile. All patients had anti-PRAME humoral responses that were not dose related, and 80% of those treated at the highest dose showed a cellular immune response. The dose of 500 μg was selected. However, further development was stopped after negative results with a similar immunotherapeutic in patients with NSCLC.